The Impact of Marketing Mix 4P’s to Consumer Switching Behavior Intention from XL to Other Network Providers - Vincent Nattaniel Kuota Kusuma (iBuss Management, 2019)
This research is about a mobile service network provider which has been operated in Indonesia for more than 20 years, namely XL. XL used to be the second leading network provider company in 2013. However, the data shown that XL has been experienced a decline in sales and performance in 2017. Therefore, the researcher would like to find solution in order to overcome the problem arises. The research study is to analyze using marketing mix 4p’s which are product, place, price, and promotion that will be the reason of consumer switching behavior intention. The researcher will ask the current user of XL and asking whether the predictors of product, place, price, and promotion affects their intention to switch to other network provider. The sampling method is using probability sampling method. There are 91 respondents that is valid and will be analyze using binary logistic regression analysis. The results has shown that only product and price that have significant impact on consumer switching behavior intention from XL to other network providers. Keywords: Product, Place, Price, Promotion, Consumer Switching Behavior Intention